Chemical profile, antiproliferative and antioxidant activities of rhizome oil of Zingiber anamalayanum from Western Ghats in India. Issue 17 (1st September 2016) - Salim, Mohamed; Kabeer, T.K. Ahmedul; Nair, S. Ajikumaran; Dan, Mathew; Sabu, M.; Baby, Sabulal
Abstract: Volatile oil from fresh rhizomes of Zingiber anamalayanum was isolated by hydrodistillation and characterised by GC–FID and GC–MS. Twenty-one out of 24 constituents comprising 99.47% of the oil were identified. Major components in Z. anamalayanum rhizome oil were δ -2-carene (52.83%), camphene (9.83%), endo-fenchol (9.42%), iso-dihydrocarveol (6.44%) and cis-p-mentha-2, 8-dien-1-ol (5.19%). Monoterpene hydrocarbons in the rhizome oil were 65.81%, followed by oxygenated monoterpenes (23.78%) and sesquiterpene hydrocarbons (9.87%). Physical parameters of rhizome oil were 1.4031, − 16.097 o ( c = 1, CHCl3 ) and 0.9202. Z. anamalayanum rhizome oil showed significant anti-Dalton's Lymphoma Ascitic activity. Abstract :